Wahana Lestari: Bil 2 2020 / Perpustakaan Tun Dr. Ismail Cawangan Johor, UiTM Johor - Abdullah, Mawar Noor; Noruddin, Nurul Amin; Mohd Azahar, Nor Azelea; Samsuri, Mohd Azmi; Md Nor, Roslan; Ibrahim, Nurul Izza (Perpustakaan Tun Dr Ismail, UiTM Johor, 2020)
ASSALAMUALAIKUM